2019
DOI: 10.1038/s41598-019-54051-y
|View full text |Cite
|
Sign up to set email alerts
|

Widespread Sexual Dimorphism in the Transcriptome of Human Airway Epithelium in Response to Smoking

Abstract: Epidemiological studies have shown that female smokers are at higher risk of chronic obstructive pulmonary disease (COPD). Female patients have worse symptoms and health status and increased risk of exacerbations. We determined the differences in the transcriptome of the airway epithelium between males and females, as well the sex-by-smoking interaction. We processed public gene expression data of human airway epithelium into a discovery cohort of 211 subjects (never smokers n = 68; current smokers n = 143) an… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
8
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
3
1
1

Relationship

1
4

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 56 publications
3
8
0
Order By: Relevance
“…DNA methylation is dynamic and is impacted by ageing, disease and environmental exposures including smoking. Sex-specific differences of DNA methylation have been described previously in blood [ 31 ] and for gene expression in lung tissue [ 22 , 48 , 49 ]. More than half of the sites we observed to have sex-specific methylation (415 loci) overlap with sites previously associated in leukocyte DNA [ 31 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…DNA methylation is dynamic and is impacted by ageing, disease and environmental exposures including smoking. Sex-specific differences of DNA methylation have been described previously in blood [ 31 ] and for gene expression in lung tissue [ 22 , 48 , 49 ]. More than half of the sites we observed to have sex-specific methylation (415 loci) overlap with sites previously associated in leukocyte DNA [ 31 ].…”
Section: Discussionmentioning
confidence: 99%
“…We did not observe significant sex-specific gene expression of our loci, although there were several genes having correlations between DNA methylation and gene expression. Differential gene expression by sex has been suggested to be limited, but differential targeting of genes via an epigenetic pathway is likely more relevant [ 22 , 58 ]. Additionally, ascertainment of this tissue cohort may limit generalizability to the general population and to other races.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Another mechanism that is proposed to contribute to cancer development is exposure to nicotine, which can promote cellular proliferation and tumor growth, migration, and invasion (Warren and Singh 2013 ). Interestingly, female sex and oral contraceptive use have been shown to alter nicotine metabolism, promoting increases in toxic nicotine metabolites; thus sex-specific xenometabolism likely contributes to increased susceptibility to tobacco smoke-related disease (Yang et al 2019 ). Finally, early in vitro work has also shown that female airway cell cultures exposed to cigarette smoke produce increased amounts of oxidants, identifying a potential driver of airway damage and lung disease onset, like cancer (Yang et al 2019 ).…”
Section: Exposure-related Sex-biased Respiratory Diseasesmentioning
confidence: 99%
“…A meta-analysis of public gene expression data sets of human airway epithelium in smokers and nonsmokers found substantial differential gene expression due to smoking status (5000+ genes), sex (100 genes), and their interaction (2600+ genes), which were independent of differences in age or pack-year history in the discovery and replication data sets (Yang et al 2019 ). The chromosomes linked to gene expression differences were not limited to sex chromosomes.…”
Section: Exposure-related Sex-biased Respiratory Diseasesmentioning
confidence: 99%